Functional literacy in higher education and labor market expectations - Moldashev, К.B.; Seithan, R.M.; Ospanova, U.А.; Myrzabekova, А.К. (BUKETOV BUSINESS REVIEW, 2023)
Object: The purpose of this study is to determine the competencies required in the labor market in the areas of information technology, finance and accounting, which will allow universities, when necessary, to revise the learning outcomes for the relevant educational programs. Methods: The main research method for this article is the content analysis of big data retrieved from www.hh.kz, which is the leading platform for job search and recruitment. Findings: Analysis was carried out using more than 1,500 vacancies in two areas: information technology and finance and accounting. The analysis showed the frequency of biograms in ads with and without work experience requirements. Further, based on the collected data, analysis, showing the frequency of key competencies practices, was conducted that were sorted from more important to less important. Conclusions: According to the results of the study in both areas of specialties, the skills of competent oral and written communication occupy a leading place. In the field of IT, employers are more likely to look for an employee who speaks English, and in the field of finance and accounting – Kazakh. Also, in the field of IT, the skills of fast learner are the most common, while in the field of finance and accounting - attentiveness, analytical skills and the ability to work with large amounts of data are in higher demand. From a digital literacy point of view, MS Excel is a necessity in finance and accounting; this requirement is not so common in IT.